The Feedback-Motivation Connection: Driving Better Speaking Outcomes for Students - Heri Alfian; Litha Nesidekawati Dakka; Aqzhariady Khartha; Muthmainnah Bahri A. Bohang (Universitas Sulawesi Barat, 2025)
This study was aimed to find out the correlation between corrective feedback, students' motivation, students’ speaking performance, and how they interplay with each other. The researcher used a mixed-method, a qualitative and quantitative design. The sample of this study was 34 third grade students of SMAN 1 Tirawuta. In collecting data, questionnaires, observation, and interviews were used. The findings showed that (1)there is a significant correlation between corrective feedback and students’ speaking performance, indicated by sig 2-tailed 0.005. (2) There is a significant correlation between students’ motivation and students’ speaking performance, indicated by sig 2-Tailed 0.003. (3) There is also a significant correlation between corrective feedback and students’ motivation and students’ speaking performance simultaneously, indicated by sig 2-tailed 0.003. The correlation between corrective feedback, students’ motivation, and students’ speaking performance were in the gravity of moderate level, R 0.559, and the R square was 0.313. This implies that 31.3 % variation of students’ speaking performance can be predicted through corrective feedback and students’ motivation, while 68.7% can be predicted through other factors. Last but not least, (4) Teacher’s feedback motivated students through their errors in improving their speaking performance